Pertanggungjawaban Pidana Korporasi terhadap Kebocoran Data Pribadi Konsumen dalam Perspektif Hukum Pidana Siber di Indonesia - Ismaidar Ismaidar; Rifqi Fairuz Ula (Lembaga Pengembangan Kinerja Dosen, 2025)
The leakage of consumers' personal data by irresponsible corporations has become a serious issue in the digital era, particularly in the context of data protection in Indonesia. This paper analyzes corporate criminal liability for such data breaches from the perspective of Indonesian cybercriminal law. The study adopts a normative legal approach through literature review of relevant legislation, legal doctrines, and court decisions. The findings indicate that corporations may be held criminally liable if proven negligent or if they fail to fulfill their data protection obligations under the Electronic Information and Transactions Law (ITE Law). Although a legal framework already exists, proving the elements of fault and direct involvement of corporate executives remains a significant challenge. Therefore, there is an urgent need for strengthened technical regulations and stricter law enforcement to ensure the protection of consumer rights in the digital sphere.